Nonlinear mechanics of crystals - Clayton, John D. 1976-; SpringerLink (Online service). (Dordrecht Springer, 2011)
This book describes behavior of crystalline solids primarily via methods of modern continuum mechanics. Emphasis is given to geometrically nonlinear descriptions, i.e., finite deformations. Primary topics include anisotropic crystal elasticity, plasticity, and methods for representing effects of defects in the solid on the material's mechanical response. Defects include crystal dislocations, point defects, twins, voids or pores, and micro-cracks. Thermoelastic, dielectric, and piezoelectric behaviors are addressed. Traditional and higher-order gradient theories of mechanical behavior of crystalline solids are discussed. Differential-geometric representations of kinematics of finite deformations and lattice defect distributions are presented. Multi-scale modeling concepts are described in the context of elastic and plastic material behavior. Representative substances towards which modeling techniques may be applied are single- and poly- crystalline metals and alloys, ceramics, and minerals. This book is intended for use by scientists and engineers involved in advanced constitutive modeling of nonlinear mechanical behavior of solid crystalline materials. Knowledge of fundamentals of continuum mechanics and tensor calculus is a prerequisite for accessing much of the text. This book could be used as supplemental material for graduate courses on continuum mechanics, elasticity, plasticity, micromechanics, or dislocation mechanics, for students in various disciplines of engineering, materials science, applied mathematics, and condensed matter physics.
Introduction -- Mathematical foundations -- Kinematics of Crystalline Solids -- Thermomechanics of Crystalline Solids -- Thermoelasticity -- Elastoplasticity -- Residual Deformation from Lattice Defects -- Mechanical Twinning in Crystal Plasticity -- Generalized Inelasticity -- Dielectrics and piezoelectricity -- Chrystal Symmetries and Elastic Constants -- Lattice Statics and Dynamics -- Discrete Defects in Linear Elasticity -- SI Units and Fundamental Constants -- Kinematic Derivations -- References -- Index.
Electronic reproduction.
Keywords: Crystals -- Mechanical properties; Nonlinear mechanics; Electronic books